Springback analysis of channel cross-sectioned bar of work-hardening materials under torsional loading. Issue 7 (3rd October 2016) - Lal, Radha Krishna; Choubey, Vikas Kumar; Dwivedi, J.P.; Singh, V.P.
Abstract : Purpose: The purpose of this paper is to deal with the springback problems of channel cross-section bars of linear and non-linear work-hardening materials under torsional loading. Using the deformation theory of plasticity, a numerical scheme based on the finite difference approximation has been proposed. The growth of the elastic-plastic boundary and the resulting stresses while loading, and the springback and the residual stresses after unloading are calculated. Design/methodology/approach: The numerical method which has been described in this paper for obtaining the solution of elasto-plastic solution can also be used for other sections. The only care that needs to be taken is to decrease the mesh size near points of stress concentration. The advantage of this technique is that it automatically takes care of all plastic zones developing over the section at different loads and gives a solution satisfying the elastic and plastic torsion equations in their respective regions. Findings: As expected, elastic recovery is found to be more with decreasing values of n and λ . The difference in springback becomes more and more with increasing values of angle of twist. The material will approach an elastic ideally plastic behavior with increasing values of λ and n . Originality/value: It seems that no attempt has been made to study residual stresses in elasto-plastic torsion of a work-hardening material for a channel cross-section.